2022
DOI: 10.3390/ijms23147863
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial Abnormalities in Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is defined as the presence in diabetic patients of abnormal cardiac structure and performance (such as left ventricular hypertrophy, fibrosis, and arrhythmia) in the absence of other cardiac risk factors (such as hypertension or coronary artery disease). Although the pathogenesis of DCM remains unclear currently, mitochondrial structural and functional dysfunctions are recognised as a central player in the DCM development. In this review, we focus on the role of mitochondrial dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 111 publications
0
14
0
Order By: Relevance
“…Since several recent studies have reported that diabetes is affected by mitophagy [ 5 , 6 , 13 , 17 , 22 , 23 , 25 , 31 ], we hypothesized that Parkin could play an important role in mitochondria in pancreatic cells in diabetes. We observed many mitophagy-related vesicles in Beta TC-6 islet cell lines treated with streptozotocin (STZ) diabetes stress through electron microscopy ( Fig 1A and 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Since several recent studies have reported that diabetes is affected by mitophagy [ 5 , 6 , 13 , 17 , 22 , 23 , 25 , 31 ], we hypothesized that Parkin could play an important role in mitochondria in pancreatic cells in diabetes. We observed many mitophagy-related vesicles in Beta TC-6 islet cell lines treated with streptozotocin (STZ) diabetes stress through electron microscopy ( Fig 1A and 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Increased lipids may promote cardiomyocyte death induced by lipotoxicity due to limited FFA oxidation ( 3 , 44 ). In addition, reactive oxygen species (ROS) and reactive nitrogen species (RNS) are produced more frequently as a result of increased intracellular fatty acid content and mitochondrial malfunction, which in turn increases OS and ERS and inhibits autophagy ( 20 , 45 , 46 ). The interaction of these effects causes ECM remodeling and fibrosis, along with cardiomyocyte loss, cardiac enlargement, and inflammation ( 47 ).…”
Section: Diabetic Cardiomyopathy: Pathogenesis Disease Progression An...mentioning
confidence: 99%
“…The interaction of these effects causes ECM remodeling and fibrosis, along with cardiomyocyte loss, cardiac enlargement, and inflammation ( 47 ). Heart stiffness, poor cardiac relaxation, and diastolic dysfunction are early signs of DCMP caused by pathophysiological anomalies ( 46 ). In addition, accumulated lipids in ECs may decrease nitric oxide (NO) bioavailability, promoting endothelial dysfunction and accelerating atherosclerosis ( 9 ).…”
Section: Diabetic Cardiomyopathy: Pathogenesis Disease Progression An...mentioning
confidence: 99%
“…DM has been reported to induce cardiac dysfunction (DM cardiomyopathy (DCM)) due to mitochondrial dysfunction [ 6 ]. Individuals with DCM are associated with an increasing risk of AF.…”
Section: Introductionmentioning
confidence: 99%